Identification of a large mud volcano field in the Hyuga-nada, northern end of the Ryukyu trench, offshore Japan - Asada, Miho; Yamashita, Mikiya; Fukuchi, Rina; Yokota, Toshiyuki; Toki, Tomohiro; Ijiri, Akira; Kawamura, Kiichiro (Frontiers in Earth Science, 2023)
We identified 27 new mud volcanoes, including potential ones, in a part of the Hyuga-nada area southwest offshore Japan, at the northern end of the Ryukyu Trench, based on subseafloor geological structures using geophysical investigations. These mud volcanoes exhibited high density and breadth and were likely connected to other mud volcano fields in the south. Acoustically investigations 2 This is a provisional file, not the final typeset article indicated subseafloor structures such that multiple acoustically transparent bodies which were interpreted as a region containing gas, appeared nearly vertical and penetrated the continuous stratigraphy. The acoustically transparent bodies were likely to appear along faults and below the bottom of valleys and sometimes reached the seafloor, then express mud volcanoes on the seafloor.They also indicated the wide distribution of the subseafloor free-gas throughout the area. These acoustic investigations suggested that the swarm of mud volcanoes exists over the Hyuga-nada area and is heterogeneously distributed along a series of plate convergent margins, the Nankai Trough and the northern part of the Ryukyu Trench.